Striving for Legitimacy Through Corporate Social Responsibility: Insights from Oil Companies - Du, Shuili (Journal of business ethics, 2012)
Being a controversial industry, oil companies turn to corporate social responsibility (CSR) as a means to obtain legitimacy. Adopting a case study methodology, this research examines the characteristics of CSR strategies and CSR communication tactics of six oil companies by analyzing their 2011–2012 web site content. We found that all six companies engaged in CSR activities addressing the needs of various stakeholders and had cross-sector partnerships. CSR information on these companies’ web sites was easily accessible, often involving the use of multimedia technologies and sometimes social media platforms. Furthermore, to boost the credibility of their CSR messages, these companies utilized a variety of tactics, such as factual arguments and two-sided messages. In sum, this research unveils the interconnectedness among business strategy, CSR practices, and CSR communication in oil companies’ attempt to gain legitimacy in an environment of controversy. The article ends with a discussion of the theoretical and practical implications of the research findings.